Expression of dnaE2 promotes genetic diversity in mycobacterial biofilms - Salini, S.; Bhat, Sinchana G.; Nijisha, M.; Paritosh, Kumar; Ramachandran, Reshma; Nikolas, Nikhil; Naz, Saba; Kurthkoti, Krishna (Frontiers in Cellular and Infection Microbiology, 2025)
The complex cellular architecture and microenvironments within biofilms give rise to a physiologically and genetically heterogeneous population. Transcriptome analysis of Mycobacterium smegmatis from biofilm culture and its transition phase into planktonic growth was performed to identify the genetic basis of heterogeneity in the biofilm. Biofilms displayed redox imbalance, resulting in increased levels of reactive oxygen species and activation of the mycobacterial mutasome consisting of dnaE2, imuA’, and imuB. Whole-genome sequencing of biofilm and planktonic cultures revealed a modest increase in the number of allelic variants in the biofilm culture compared with the planktonic culture. Deletion of dnaE2 reduced mutation frequency and bacterial fitness compared with the parental strain in biofilm culture and reduced allelic variation in the culture. Our study uncovered the multiple benefits of dnaE2 expression in biofilms, such as increased genetic diversity and reduced growth rate, both of which are necessary for mycobacterial survival and adaptation.